MENGUBAH WAJAH FIKIH ISLAM - Ghazali, Abd Moqsith (Khatulistiwa, 2013)
Islamic fiqh as a part of Islamic studies is a product of thought which always serves as an interaction between a thinker and the socio-political environment that surround him. It is in this situation that the whole Islamic fiqh is written. This is why Imam Syafi‟i for example had a different fiqh opinion; Qawl qadim and Qawl jaded. Qawl qadim is the opinion of imam syafi‟i when he was in Baghdad, while Qawl jaded is the view of imam Syafi‟i while he has living in Egypt. Therefore, it seems logical that the classical fiqh thought is put into the configuration and the general context when fiqh is produced on the one hand, and in the context of a particular epistemology on the other hand.